MENIMBANG RASA KEADILAN HUKUM DI INDONESIA: KOMPARASI DENGAN PANDANGAN ISLAM: (Considering the Sense of Legal Justice in Indonesia: Comparison with Islamic Views) - Baeti Rohman; Fikri Maulana (Raqib: Jurnal Studi Islam, 2024)
Law is one of the important pillars of democracy, strong law enforcement will encourage the creation of a strong democracy. The most important value of law is the value of justice, in fact justice is the main goal of the law itself, the law exists to create justice in a country, before the law, all citizens must receive the same treatment, privileging certain parties is not known in legal logic. In practice in Indonesia, currently law is a field that is being widely highlighted, debates about the extent to which a sense of justice is applied in law enforcement are busy, in general there is a division of opinion in society, one party considers law enforcement to have brought justice to all groups, while Other parties actually hold the opposite view, the law is considered not to bring justice to all levels of society. In an Islamic perspective, fair enforcement for all groups of society in a country is an obligation, the government which carries out its mandate is required to be fair in enforcing the law, disobedience to the law not only brings world consequences but also consequences in the afterlife.